3-Dimensional coculture of breast cancer cell lines with adipose tissue–Derived stem cells reveals the efficiency of oncolytic Newcastle disease virus infection via labeling technology - Salman, Marwa Ibrahim; Al-Shammari, Ahmed Majeed; Emran, Mahfodha Abbas (Frontiers in Molecular Biosciences, 2022)
Oncolytic virotherapy is one of the emerging biological therapeutics that needs a more efficient in vitro tumor model to overcome the two-dimensional (2D) monolayer tumor cell culture model’s inability to maintain tissue-specific structure. This is to offer significant prognostic preclinical assessment findings. One of the best models that can mimic the in vivo model in vitro are the three-dimensional (3D) tumor–normal cell coculture systems, which can be employed in preclinical oncolytic virus therapeutics. Thus, we developed our 3D coculture system in vitro using two types of breast cancer cell lines showing different receptor statuses cocultured with adipose tissue–derived mesenchymal stem cells. The cells were cultured in a floater tissue culture plate to allow spheroids formation, and then the spheroids were collected and transferred to a scaffold spheroids dish. These 3D culture systems were used to evaluate oncolytic Newcastle disease virus AMHA1 strain infectivity and antitumor activity using a tracking system of the Newcastle disease virus (NDV) labeled with fluorescent PKH67 linker to follow the virus entry into target cells. This provides evidence that the NDV AMHA1 strain is an efficient oncolytic agent. The fluorescently detected virus particles showed high intensity in both coculture spheres. Strategies for chemically introducing fluorescent dyes into NDV particles extract quantitative information from the infected cancer models. In conclusion, the results indicate that the NDV AMHA1 strain efficiently replicates and induces an antitumor effect in cancer–normal 3D coculture systems, indicating efficient clinical outcomes.